Separation and Quantification of a Natural Drug Component Against Human Pathogens from Aristolochia bracteolata Lam - R.D. Jebakumar, Solomon; Vimalan, Jayaraj; Senthil Kumar, R. (Asian Journal of Chemistry, 2010)
Aristolochia bracteolata Lam, whole plant was subjected to Soxhlet extraction with solvents like chloroform, acetone and methanol. Subsequently the extracted solvent phases were passed through thin layer chromatography and three distinct spots were separated as C1, A1 and M2, respectively. Among all the three independent compounds C1, A1 compounds showed maximum level of antimicrobial activity against the bacterial pathogens like methicillin resistant Staphylococcus aureus (MRSA), Salmonella typhi and Aspergillus mucor. Among all tested compounds C1 and M2 showed ten fold increased activity than A1 compound. The 1H NMR analysis of the purified active compounds C1, A1 and M2, clearly shows that all the three compounds are independent. The HPLC and NMR results confirm that these three compounds are pure and entirely different from each other. 1H NMR analysis individually confirmed that C1, A1 and M2 compounds are pure and aliphatic in nature.